PENGARUH PENGGUNAN MODEL COOPERATIVE LEARNING TYPE COURSE RIVIEW HORAY (CRH) TERHADAP HASIL BELAJAR IPS TERPADU PESERTA DIDIK KELAS VIII SEMESTER GENAP SMP NEGERI 1 KOTAGAJAH TAHUN PELAJARAN 2018/2019 - Marina Dwi Susanti; Ningrum Ningrum; Wakijo Wakijo (EDUNOMIA: Jurnal Ilmiah Pendidikan Ekonomi, 2021)
Based on the results of the re-survey in SMP Negeri 1 Kotagajah which became the problem in this study there are still many class students who have not completed the Integrated Social Studies Learning outcomes at the even Semester of the eight grade of SMP Negeri 1 Kotagajah in the academic year 2018/2019. The purpose of the study is to determine the influence of Cooperative Learning Type Course Rivew Horay (CRH) model in Integrated Social Studies learning outcomes at the even Semester of SMP Negeri 1 Kotagajah in the academic year 2018/2019. This study uses the experimental metod (Quasy Experimental), with the form of the experimental design type Nonequivalent Control Goup Design. The results of the research conducted state that the hypothesis is accepted, with a tcount > ttable that can seen in the appendix list G, at a significant level of 5% which is 4,33 > 1,699. Students who are completed with KKM are 65 after being given treatment with Cooperative Learning Type Course Rivew Horay model (CRH) 26 studens with a percentage of 88,87%, while unfinished students as many as 5 students with a percentage of 16,23%. This indicating that there is epositive influence in using the Cooperative Learning Type Course Rivew Horay’s model on leraning outcomes of integrated social students subject at the even semester of the eight grade of SMP Negeri 1 Kotagajah in the academic year 2018/2019